2013
DOI: 10.1152/japplphysiol.00889.2013
|View full text |Cite
|
Sign up to set email alerts
|

A selective 5-HT1areceptor agonist improves respiration in a mouse model of Rett syndrome

Abstract: Rett syndrome is a neurological disorder caused by loss of function mutations in the gene that encodes the DNA binding protein methyl-CpG-binding protein 2 (Mecp2). A prominent feature of the syndrome is disturbances in respiration characterized by frequent apnea and an irregular interbreath cycle. 8-Hydroxy-2-dipropylaminotetralin has been shown to positively modulate these disturbances (Abdala AP, Dutschmann M, Bissonnette JM, Paton JF, Proc Natl Acad Sci U S A 107: 18208-18213, 2010), but the mode of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 34 publications
1
35
0
1
Order By: Relevance
“…KO animals also exhibit decreased GABA levels in some areas of their brains (57,131), and administration of the GABA reuptake inhibitor NO-711 resulted in a four-fold decrease in apnea frequency (132). Serotonin receptor agonists have also been successful in ameliorating the breathing abnormalities of KO animals (132,133).…”
Section: From Patient To Protein: the Molecular Function Of Mecp2mentioning
confidence: 99%
“…KO animals also exhibit decreased GABA levels in some areas of their brains (57,131), and administration of the GABA reuptake inhibitor NO-711 resulted in a four-fold decrease in apnea frequency (132). Serotonin receptor agonists have also been successful in ameliorating the breathing abnormalities of KO animals (132,133).…”
Section: From Patient To Protein: the Molecular Function Of Mecp2mentioning
confidence: 99%
“…Banghart et al (2004) demonstrated the first optogenetic pharmacological photoswitches, SPARK, which is attached to an engineered K + channel. Since then, the same strategy has been extended to target the photoswitches to other K + channels (Fortin et al 2011, Sandoz et al 2012, ionotropic and metabotropic glutamate receptors (Levitt et al 2013, Volgraf et al 2007, and nicotinic acetylcholine receptors .…”
Section: Chemical-based Photoswitchesmentioning
confidence: 99%
“…Apparently, the age does not correlate well with the early onset of RTT in humans. In another study, breathing abnormalities were observed in Mecp2 ?/-mice 6-17 months, which were reduced by the selective 5HT-1a agonist, F15599 [14].…”
Section: Discussionmentioning
confidence: 99%